The influence of service quality, brand image and consumer satisfaction on repurchase interest at Pondok Kelapa Pizza Hut Restaurant, East Jakarta - Syaiful Bahri; Resti Hardini; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of service quality, brand image and customer satisfaction on repurchase interest in the hut pizza restaurant pondok kelapa, East Jakarta. This study uses quantitative research methods. This study uses primary data by distributing questionnaires. The population in this study were the general public who had bought a pizza hut product once at a pizza hut restaurant in a coconut hut. The questionnaire was distributed to 100 respondents. The analysis technique used is quantitative analysis with the data test used is multiple linear regression, several hypothesis tests and using the staticial product and service solution (SPSS) program version 25.0. The results of the study state that service quality has a positive and significant influence on repurchase interest. Partially, it has a positive and significant influence on repurchase interest in the hut pondok kelapa pizza restaurant. Meanwhile, simultaneously service quality, brand image and customer satisfaction have a significant influence on repurchase interest in restorant pizza hut pondok kelapa, East Jakarta.